A Brainstem reticulotegmental neural ensemble drives acoustic startle reflexes - Weiwei Guo (Nature Portfolio, 2021)
The function of brainstem reticulotegmental nucleus (RtTg) and its related circuits are not fully understood. Here, the authors report a cochlear nucleus-RtTg-spinal motor neuron circuit that specifically mediates acoustic startle reflexes.